From skeletal muscle damage and regeneration to the hypertrophy induced by exercise: what is the role of different macrophage subsets? - Araujo Minari, Andre Luis [UNESP] (2022)
Macrophages are one of the top players when considering immune cells involved with tissue homeostasis. Recently, increasing evidence has demonstrated that macrophages could also present two major subsets during tissue healing: proliferative macrophages (M1-like), which are responsible for increasing myogenic cell proliferation, and restorative macrophages (M2-like), which are involved in the end of the mature muscle myogenesis. The participation and characterization of these macrophage subsets are critical during myogenesis to understand the inflammatory role of macrophages during muscle recovery and to create supportive strategies that can improve mass muscle maintenance. Indeed, most of our knowledge about macrophage subsets comes from skeletal muscle damage protocols, and we still do not know how these subsets can contribute to skeletal muscle adaptation. Thus, this narrative review aims to collect and discuss studies demonstrating the involvement of different macrophage subsets during the skeletal muscle damage/regeneration process, showcasing an essential role of these macrophage subsets during muscle adaptation induced by acute and chronic exercise programs.